2018
DOI: 10.1177/2158244018820386
|View full text |Cite
|
Sign up to set email alerts
|

Developing College EFL Writers’ Critical Thinking Skills Through Online Resources: A Case Study

Abstract: This study reports on how the supplementation of online resources, informed by systemic functional linguistics (SFL), impacted English-as-a-foreign-language (EFL) student writers' development of critical thinking skills. Through qualitative analyses of student-teacher interactions, interviews with students, and students' written documents, the case study shows that through 1 semester of intensive exposure to SFL-based online resources in a college Chinese EFL writing classroom, EFL writers were able to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Critical thinking is thinking clearly and rationally. The ability to think critically is not an inherent ability of humans from birth, but is something that must be trained so that efforts need to be made to improve this ability [42] [43]. Critical thinking has several characteristics [44], namely a) able to analyze arguments, b) able to make a conclusion using inductive/deductive reasoning, c) able to make assessments and evaluations, d) able to make decisions and solve problems.…”
Section: Critical Thinking Abilitymentioning
confidence: 99%
“…Critical thinking is thinking clearly and rationally. The ability to think critically is not an inherent ability of humans from birth, but is something that must be trained so that efforts need to be made to improve this ability [42] [43]. Critical thinking has several characteristics [44], namely a) able to analyze arguments, b) able to make a conclusion using inductive/deductive reasoning, c) able to make assessments and evaluations, d) able to make decisions and solve problems.…”
Section: Critical Thinking Abilitymentioning
confidence: 99%
“…Despite the importance of critical thinking skills for English Department students and students learning English as a second or foreign language in general, several studies suggest that their critical thinking skills are not yet satisfactory [4] [26] [27] as proved by their performance in the class. They might score well in the exam but fail in employing critical thinking skills to solve their daily problems.…”
Section: The Critical Thinking Skills Of English Department Studentsmentioning
confidence: 99%
“…They might score well in the exam but fail in employing critical thinking skills to solve their daily problems. In a study carried out in an EFL writing class in China, [27] found out that students' low achievement in writing was due to the inadequate exposure to activities which develop critical thinking skills. Critical thinking skills are often ignored in the writing process for the learning process is focused more on grammar and structure materials, causing the students to have little chances to develop effective essays.…”
Section: The Critical Thinking Skills Of English Department Studentsmentioning
confidence: 99%
“…However, several previous studies are in line with the findings of this study. Students as writers can develop critical thinking skills even though, in practice, they face various challenges (Zhang, 2018). Unlike these findings, Bouanani (2015) also states that critical thinking can be improved through dialogue and reflective writing.…”
Section: Findings and Discussionmentioning
confidence: 99%